Pembinaan Kelompok Peternak Itik Monggelemong Sebagai Penghasil Telur Organik - Tamzil, Mohammad Hasil; Budi Indarsih; Syamsuhaidi (Universitas Mataram, 2024)
The supply of organic agricultural products is relatively less than non-organic products. This reason was the basis for this coaching activity to be carried out. The coaching activities has been carried out continuously since 2013. The program started with conducting research on alternative feed ingredients at the targeted location. The following programs were the down streaming of research results at the research location. The next coaching activity was efforts on improving the housing system, housing environment, post-harvest processing by introducing natural feed stuff using green algae, packaging and marketing. Some of the eggs produced were marketed to outside groups and some were processed into salted eggs and labeled with the name